Associations of Vitamin D With GPX4 and Iron Parameters in Chronic Obstructive Pulmonary Disease Patients: A Case–Control Study - Jun Fei; Ling Liu; Jia-Fei Li; Qiang Zhou; Yu Wei; Ting-Dong Zhou; Lin Fu (Canadian Respiratory Journal)
Conclusions: Vitamin D deficiency is positively associated with GPX4 reduction and iron parameters elevation in COPD patients. It is recommended to explore the role of vitamin D supplementation in the progression of COPD.